Influência do estímulo gustativo na pressão de sucção de recém-nascidos - Segala, Fernanda (2020)
Most of the protocols used to determine readiness for oral feeding in newborn infants, especially those born preterm, include an assessment of non-nutritive sucking. The use of taste stimulation during this assessment may influence the oral performance of infants. The aim of this study was to verify the influence of taste stimulation on sucking pressure during the quantitative assessment of non-nutritive sucking in newborn infants. The study included 60 healthy full-term infants of both sexes, divided into two groups, one with taste stimulation and the other without, for the assessment of mean and maximum non-nutritive sucking pressure. The taste stimulus used was maternal breast milk. Mean and maximum non-nutritive sucking pressure were measured using the S-FLEX® device (an infant sucking pressure monitor). The results revealed that both mean and maximum sucking pressure were significantly higher in newborns exposed to the taste stimulus during non-nutritive sucking than in those who did not receive gustatory stimulation. These findings show that taste stimulation during the assessment of non-nutritive sucking increases the sucking pressure of full-term infants, and may improve their oral feeding skills.